(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Academic services are essential resources for student nurses in their studies. These services are institutional methods which include the structure, rules, and regulations in the provision of academic services. Instructional services are skills and tools to enhance the knowledge, skills and attitude of student nurses. School resources are provided to students to improve their knowledge, skills and attitude. The study determined the level of satisfaction of student nurses on the academic services in the school of nursing in terms of institutional method, instructional services, and school resources, the factors that influence the academic performance of student nurses, and the difference in the level of satisfaction of the student nurses on the academic services in the school of nursing when respondents are grouped according to gender and year level. The study utilized a descriptive-survey design involving 187, first year to fourth year Bachelor of Science in Nursing students. A self-made questionnaire was used as the data gathering tool in this study. The findings of the study showed that students are moderately satisfied with the academic services rendered in the school of nursing. Teachers’ commitment and student time management influence student nurses’ satisfaction on the academic services in the school of nursing. Furthermore, the findings showed that gender, and year level has no significant effect on the level of satisfaction of student nurses on the academic services in the school of nursing. The findings imply the need for a continuous innovation of the academic services in the school of nursing.